Perceptions and Motivations for Buying and Selling Disputed Land in Sampit City Central Kalimantan an Islamic Economic Perspective - Rivaldo, Ahmad; Sadikin, Ali; Zulkifli, Zulkifli; Safitri, Novi Angga; Hafizi, Muhammad Riza (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the practice of buying and selling disputed land, understand the perceptions and motivations of the transaction actors, and examine these problems from an Islamic economic perspective. This research uses a descriptive qualitative approach through a field research method with data collection techniques in the form of observation, in-depth interviews, and documentation of a number of informants selected purposively. The results show that the practice of buying and selling disputed land takes place informally, with proof of transactions in the form of receipts and personal trust between individuals. Community perceptions tend to be permissive, considering the transaction valid as long as it is done voluntarily, even without an official certificate. The main motivation of the perpetrators is the low price of the land, the strategic location, and the belief that the legal status of the land can be resolved at a later date. From an Islamic economic perspective, this practice contains elements of gharar (uncertainty), which is prohibited due to the lack of clarity of ownership. In conclusion, this practice shows the lack of public awareness of Sharia law and land regulations. Therefore, legal education, socialization of Islamic economics, and enforcement of regulations are needed so that land transactions run according to the principles of justice and benefit.